Conversion Improvement of Propylene to Acrylic Acid Process - Mohamad Syarif Farhan; Alfredo Daniel Alexander Tuhervan Barus; Alegi Hilmy Bahij; Kevin Benget Parulian Nadeak (Journal of Chemical Engineering Research Progress, 2025)
Acrylic acid (C3H4O2) is a chemical compound used widely in industry. This study aims to develop a modifed process for Arcylic Acid production through direct oxidation. The objective is to improve Acrylic Acid conversion over conventional methods. Process modeling and simulation were conducted using Aspen Plus, and the systems were optimized for operating conditions. In conclusion, both proposed methods offer viable and environmentally favorable alternatives for sustainable proyplene production, with the DC2M route offering superior economic performance. Copyright © 2025 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).